The Impact of Capital Structure on Non-Financial Firms Performance: Evidence from South Africa - Awah, Stephanie (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
This research studies the impact of capital structure on firms’ performance, based on a sample of 30 South African firms listed on the Johannesburg stock exchange market during the period 2009-2014. The performance measures used are; return on equity (ROE), return on asset (ROA), and Tobin’s Q ratio which are the dependent variables. Total debt ratio (TDR), long term debt ratio (LTDR), short term debt ratio (STDR), debt to equity ratio (D/E) and size have been used as measures of capital structure. By using the random effect panel data regression method, we found that ROE is significantly negatively related to TDR and D.E ratio. Also, Tobin’s Q is positively related to STDR and negatively related to size. However, there is no statistical significant relation between ROA and capital structure of firms. Aside from the positive relationship between Tobin’s Q and STDR, we can conclude that capital structure has a negative impact on firms’ performance. Keywords: Capital structure, Firm performance, Return on Equity, Return on Asset, Tobin’s Q.

ÖZ: Bu çalışma 2009-2014 yılları arası JohannesburgBorsasında işlem gören 30 Güney Afrika firmasının sermaye yapılarınınperformansınasıl etkilediğini incelemiştir. Kullanılan performans ölçütleri(bağımlı değişkenler); Özkaynak getirisi (ROE) Varlık getirisi (ROA) ve Tobin Q oranıdır. Toplam borç oranı (TDR), uzun vadeli borç oranı (LTDR), kısa vadeli borç oranı (STDR), sermaye borç oranı (D / E) ve şirket büyüklüğü sermaye yapısı ölçütleri olarak kullanılmıştır. Çalışmada rastgele (random) etki panel veri regresyon yöntemi kullanılmıştır. Çalışma sonuçları ROE anlamlı ölçüde TDR ve D/E oranı ile olumsuz olarak ilişkili olduğunu göstermektedir. Çalışmada ayrıca, TobinQ’nunSTDR’dan pozitif, şirket büyüklüğünden ise negatif etkilediğiistatistiki olarak anlamlı bulunmuştur. Ancak, ROA ve firmaların sermaye yapısı arasında istatistiksel olarak anlamlı bir ilişki bulunamamıştır. Sonuç olarak Tobin Q ve STDR arasında pozitif ilişki dışında, araştırmada kullanılan şirketlerin sermaye yapılarının şirket performansına olumsuz etki yaptığı sonucu ortaya çıkmaktadır. Anahtar Kelimeler: Sermaye yapısı, Firma performansı, Özkaynak kârlılığı, Aktif karlılığı, Tobins Q.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2016. Supervisor: Prof. Dr. Mustafa Besim.
Keywords: Banking and Finance; Banks and Banking-South Africa; Capital structure; Firm performance; Return on Equity; Return on Asset; Tobin’s Q